Changes in the conditioning components for the Japanese Universiade swimming teams - Jigami, H.; Kato, T.; Koizumi, K.; Kaneoka, K. (XIIth International Symposium for Biomechanics and Medicine in Swimming, 2014)
Most injuries occurring in competitive swimmers are caused by overuse. Some studies have reported injuries in competitive swimmers. In Japan, Muto et al. conducted medical checkups for national team swimmers who participated in the 1990 Asian games. They reported that 68.8% of swimmers had injuries and that the low back region was the most frequently affected body part (1992, Written in Japanese). In addition, 56.1% of swimmers who participated in the 2008 Olympic games had injuries, with the low back region being the most frequently affected. In contrast, injury survey reports for the national swimming team of the United States have mentioned that approximately 70% of national team swimmers had shoulder girdle injury and that 57% of swimmers who participated in the world championship games had shoulder girdle injurll2 l. Thus, the prevalence of injury and the injured parts are different even among top swimmers. This discrepancy may be caused by the differences in the support system of each country. The Japan Institute of Sports Sciences (JISS) and the National Training Center (NTC) were established as centers for sports sciences, sports medicine, and information. The JISS promotes research activities and provides support for athletes and sports instructors, in cooperation with the Japanese Olympic Committee, sports federations, universities, and sports research institutions and organisations. The NTC is also a base for strengthening the performance of top-level athletes, enabling them to undergo intensive continuous training. The national swimming team also uses the facilities and support systems of JISS and NTC. Since 2001, the national swimming team has performed training camps at the JISS and NTC to improve competitive level and conditioning. These efforts help to not only improve competitive level but also prevent injury in swimmers. Because of these support activities, the incidence and locations of injuries have changed; however, these details have not been reported. In addition, it is important to longitudinally analyze conditioning components and the number of conditioning techniques used while developing injury prevention programs for swimmers. Because most previous studies among swimmers were cross-sectional surveys, data verifying the effects of injury prevention programs and the conditioning components for swimmers are insufficient. The present study aimed to verify the longitudinal changes in the type and number of conditioning components for high-level Japanese swimmers.